Cosmopolitanisms and Latin America Against the Destiny of Place - Loss, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
This book examines Latin America's history of engagement with cosmopolitanisms as a manner of asserting a genealogy that links cultural critique in Latin America and the United States. Cosmopolitanism is crucial to any discussion of Latin America, and Latin Americanism as a discipline. Reinaldo Arenas and Diamela Eltit become nodal points to discuss a wide range of issues that include the pedagogical dimensions of the DVD commentary track, the challenges of the Internet to canonization, and links between ethical practices of Benetton and the U.S. academy. These authors, whose rejection of the comfort of regimented constituencies results in their writing being perceived as raw, vindictive, and even alienating, are ripe for critique. What they say about their relation to place with regard to their products' national and international viability is central. The book performs what it theorizes. It travels between methodologies, hence bridging the divide between cosmopolitanism and that alleged common space of Latin American identity as per the colonial experience, illustrating cosmopolitanism as a mediating operation that is crucial to any discussion of Latin America, and of Latin Americanism as a discipline.
Keywords: Ethnology—Latin America; Civilization—History.; Ethnicity; America—History.; Sociology; United States—Study and teaching; Latin American Culture; Cultural History; Ethnicity Studies; History of the Americas; Sociology, general; American Culture